Adaptive Sliding Mode Observer for Nonlinear Interconnected Systems with Time Varying Parameters. Issue 1 (4th December 2018) - Mohamed, Mokhtar; Yan, Xing‐Gang; Mao, Zehui; Jiang, Bin
Abstract: In this paper, a class of nonlinear interconnected systems with uncertain time varying parameters (TVPs) is considered. Both the interconnections and the isolated subsystems are nonlinear. Sliding mode control method and adaptive techniques are employed together to design an observer to estimate the state variables of the systems in presence of unknown TVPs. The Lyapunov direct method is used to analysis the stability of the sliding motion and it is not required to solve the so‐called constrained Lyapunov problem (CLP). A set of conditions is developed under which the augmented systems formed by the error dynamical systems and the designed adaptive laws, are globally uniformly ultimately bounded. A simulation example is presented and the results show that the method proposed in this paper is effective.